2020
DOI: 10.5114/ada.2019.83655
|View full text |Cite
|
Sign up to set email alerts
|

Expression of eosinophils, RANTES and IL-25 in the first phase of Hymenoptera venom immunotherapy

Abstract: Introduction: Venom immunotherapy (VIT) can protect against severe anaphylactic reactions (SR) in 80-100% of subjects allergic to Hymenoptera venom. The mechanisms of induction of immunological tolerance produced by VIT are still little known. It has been shown that VIT modulates Treg activity, Th2 or Th1 cells or both, increases production of IL-10, decreases secretion of IL-13, and causes an IgG4/IgE ratio shift. Aim: To investigate the blood eosinophil count, CCL5/RANTES and IL-17E/IL-25 concentrations befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…27 Two AITinduced chemokines, CCL-5 (RANTES), and CCL-23 (MIP3), which are known to be involved in macrophage chemotaxis and were reported to be elevated in serum samples of patients receiving (insect venom) immunotherapy, were also detected in-and off-season. 28 CCL-5 is a major regulator of suppressive immune programs 29 and may contribute to antagonize pro-allergic type-2 immunity by recruiting Th1 cells as well as regulatory T cells. 30 The atypical chemokine receptor ACKR2, 30 the major CCL-5 scavenger receptor, is decreased through AIT and further increases the biological activity of CCL5.…”
Section: Ait-induced Local Changes In Off-seasonmentioning
confidence: 99%
“…27 Two AITinduced chemokines, CCL-5 (RANTES), and CCL-23 (MIP3), which are known to be involved in macrophage chemotaxis and were reported to be elevated in serum samples of patients receiving (insect venom) immunotherapy, were also detected in-and off-season. 28 CCL-5 is a major regulator of suppressive immune programs 29 and may contribute to antagonize pro-allergic type-2 immunity by recruiting Th1 cells as well as regulatory T cells. 30 The atypical chemokine receptor ACKR2, 30 the major CCL-5 scavenger receptor, is decreased through AIT and further increases the biological activity of CCL5.…”
Section: Ait-induced Local Changes In Off-seasonmentioning
confidence: 99%
“…Venom immunotherapy (VIT) could prevent severe allergic reactions in 80–100% subjects allergic to Hymenoptera venom. An immunological study on the early phase of VIT performed on forty individuals indicated that cytokines (CCL5/RANTES and IL-17E/IL-25) and eosinophils were conducive to the immune response ( Palgan et al, 2020 ).…”
Section: Safety and Venom Immunotherapymentioning
confidence: 99%